Software test effort estimation: a model based on cuckoo search. (1st January 2012) - Srivastava, Praveen Ranjan; Varshney, Abhishek; Nama, Priyanka; Yang, Xin-She
Test effort estimation is the process of predicting effort for testing the software. It has always been a fascinating area for software engineering researchers. "How long will it take to test the system?" is the most promising question in minds of testers before the testing process actually starts. Many factors such as the productivity of the test team, strategy chosen for testing, the size and complexity of the system, technical factors, and expected quality can affect test effort estimation. Testing requires a good amount of time and effort in the entire software development life cycle. Several researches have attempted to develop test effort estimation models but still it is not possible to achieve accurate forecasting. A new model based on a metaheuristic technique called, cuckoo search, for estimating the test effort is proposed in this paper. The proposed model is used to assign weights to the various factors involved based on past results, and, is then used for predicting the test effort for new projects of similar kind.